Влияние размера частиц горной породы на параметры пневмотранспортирования - Пономаренко, С.Н. (Геотехническая механика, 2012)
Приведені результати досліджень впливу розміру часток гірської породи, що транспортується, на параметри пневмотранспортування. Отримані залежності для визначення швидкості пневмотранспортування та витрат стислого повітря від розміру часток матеріалу, що транспортується, з урахуванням параметрів пневмотранспортної системи. The brought results over of researches of influence of size of parts of mountain breed that is
transported, on the parameters of pneumatic portage. The got dependences are for determination of speed of pneumatic portage and charges of the compressed air from the size of parts of material that is transported, taking into account the parameters of the pneumatic portage system.